The Impact of Speech Clichés (on the Material of Constitutions of the Soviet and Post-Soviet Periods) (Proceedings of Southern Federal University. Philology, 2020)
Speech impact with the anthropocentric approach significantly expands its boundaries. Studying the ideologically oriented Constitutions of the Soviet and post-Soviet periods from the position of pragmalinguistics, a speech impact was revealed through an ideologized speech cliche. This concept is understood as a ready-to-use speech formula that is deliberately introduced into the collective subconscious of the speakers of a given language and capable of exercising an emotionally-evaluative impact on the text recipient. A perlocutionary pragmalinguistic experiment was conducted to determine the emotional-evaluative attitude of representatives of two different generations (retired military and graduates of secondary schools) towards ideologized speech cliches in the Constitutions of the Soviet and post-Soviet periods. In this experiment, the preambles were investigated - the introductory parts of five Constitutions (K. of the RSFSR of 1918, K. of the USSR of 1924, K. of the USSR of 1936, K. of the USSR of 1977, and K. of the Russian Federation of 1993), in which many ideologized speech clichés were concentrated.Keywords: speech impact, ideologized speech clichés, pragmalinguistics, the Constitution, emotional evaluative attitude.DOI 10.18522/1995-0640-2020-1-85-92